Analisis Peran Guru dalam Pembelajaran Abad 21 pada Siswa Sekolah Dasar di Kurikulum Merdeka - Siti Nur Maulidah; Muhammad Aqil Madani; Najwa Nabilah; Muhammad Ridho Ramadhan Ali; Ikmawati Ikmawati; Zainuddin Untu (Universitas Maritim AMNI Semarang, 2024)
This research aims to describe the role of teachers in 21st century learning for elementary school students in the independent curriculum. In this research, the method used is qualitative descriptive analysis with a library research approach, namely an approach that focuses on literature analysis. Researchers collect data from various written sources such as books, journals and other references. Based on the research results, it shows that in 21st century learning teachers have a very important and crucial role in the learning process and development of students' skills based on 4C skills (communication, critical thinking, collaboration and creativity). It is hoped that 21st century learning for elementary school students through the independent curriculum can develop students' potential and skills to compete with developments that are increasingly developing day by day. The implementation of the independent curriculum in elementary schools also plays a role in creating empowered students, able to adapt to current developments through a project to strengthen the profile of Pancasila students. Therefore, it is hoped that there will be collaboration and support from parents, school principals and the government so as to produce a young generation who are intelligent, have character and are ready to face the future. Abstrak. Penelitian ini bertujuan untuk mendeskripsikan bagaimana peran guru dalam pembelajaran abad-21 pada siswa sekolah dasar di kurikulum merdeka. Dalam penelitian ini, metode yang digunakan adalah analisis deskriptif kualitatif dengan pendekatan library research, yaitu pendekatan yang berfokus pada analisis literatur. Peneliti mengumpulkan data dari berbagai sumber tertulis seperti buku, jurnal, dan referensi lainnya. Berdasarkan hasil penelitian menunjukkan bahwa dalam pembelajaran abad-21 guru memiliki peran yang sangat penting dan krusial dalam proses pembelajaran dan pengembangan keterampilan siswa berdasarkan keterampilan 4C (communication, critical thinking, collaboration, dan creativity). Pembelajaran abad-21 pada siswa sekolah dasar melalui kurikulum merdeka diharapkan dapat mengembangkan potensi dan keterampilan siswa untuk bersaing dengan perkembangan zaman yang kian hari makin berkembang. Implementasi kurikulum merdeka di sekolah dasar juga berperan untuk menciptakan siswa yang berdaya, mampu beradaptasi dengan perkembangan zaman melalui projek penguatan profil pelajar Pancasila. Oleh karena itu diharapkan adanya kolaborasi dan dukungan dari orang tua, kepala sekolah dan pemerintah sehingga menghasilkan generasi muda yang cerdas, berkarakter, dan siap menghadapi masa depan.